Інтегральні зображення розв'язків стаціонарних задач теплопровідності для обмежених багатошарових циліндричних тіл - Конет, І.М. (Видавничий дім "Академперіодика" НАН України, 2007)
The exact analytical solution of a stationary heat problem for limited multilayer cylindrical solids is constructed by the method of integral transformations.